The relationship between job satisfaction and job turnover intention among employees in Tenaga Nasional Berhad (TNB) Pasir Gudang / Anis Hamizah Abdul Rahman - Abdul Rahman, Anis Hamizah (Faculty of Business and Management, 2015)
This quantitative research aims to examine the impact of job satisfaction through working condition, work value, co-worker, and supervisor that influence job turnover intention among employees. This includes the objectives as follows, to determine the relationship between extrinsic job satisfaction and turnover intention, and also to determine the relationship between intrinsic job satisfaction and turnover intention. Most of the intention of employee to have job turnover are influence by surrounding factors such their co-worker and supervisor. These two factors are the main factor that always seen roughly by the employer. But there are other factors that influence to job turnover such working condition. The data has been collected from employees at TNB Pasir Gudang which include executive and non-executive employees by distributing questionnaire to the 128 employees that been selected randomly. The results showed that all independent variables for this study which are work value, working condition, supervisor and co-worker are significant with job turnover intention. This study is said to be beneficial to the company in order to reduce the number of employee turnover intention. Recommendation for future is also have been discussed.